Hepatocyte-Specific Deletion of TIPARP, a Negative Regulator of the Aryl Hydrocarbon Receptor, Is Sufficient to Increase Sensitivity to Dioxin-Induced Wasting Syndrome. (4th June 2018) - Hutin, David; Tamblyn, Laura; Gomez, Alvin; Grimaldi, Giulia; Soedling, Helen; Cho, Tiffany; Ahmed, Shaimaa; Lucas, Christin; Kanduri, Chakravarthi; Grant, Denis M; Matthews, Jason
Abstract: The aryl hydrocarbon receptor (AHR) mediates the toxic effects of dioxin (2, 3, 7, 8-tetrachlorodibenzo- p -dioxin; TCDD), which includes thymic atrophy, steatohepatitis, and a lethal wasting syndrome in laboratory rodents. Although the mechanisms of dioxin toxicity remain unknown, AHR signaling in hepatocytes is necessary for dioxin-induced liver toxicity. We previously reported that loss of TCDD-inducible poly(adenosine diphosphate [ADP]-ribose) polymerase (TIPARP/PARP7/ARTD14), an AHR target gene and mono-ADP-ribosyltransferase, increases the sensitivity of mice to dioxin-induced toxicities. To test the hypothesis that TIPARP is a negative regulator of AHR signaling in hepatocytes, we generated Tiparp fl/fl mice in which exon 3 of Tiparp is flanked by loxP sites, followed by Cre-lox technology to create hepatocyte-specific ( Tiparp fl/fl Cre Alb ) and whole-body ( Tiparp fl/fl Cre CMV ; Tiparp Ex3−/− ) Tiparp null mice. Tiparp fl/fl Cre Alb and Tiparp Ex3−/− mice given a single injection of 10 μg/kg dioxin did not survive beyond days 7 and 9, respectively, while all Tiparp +/+ mice survived the 30-day treatment. Dioxin-exposed Tiparp fl/fl Cre Alb and Tiparp Ex3−/− mice had increased steatohepatitis and hepatotoxicity as indicated by greater staining of neutral lipids and serum alanine aminotransferase activity than similarly treated wild-type mice. Tiparp fl/fl Cre Alb and Tiparp Ex3−/− mice exhibited augmented AHR signaling, denoted by increased dioxin-induced gene expression. Metabolomic studies revealed alterations in lipid and amino acid metabolism in liver extracts from Tiparp fl/fl Cre Alb mice compared with wild-type mice. Taken together, these data illustrate that TIPARP is an important negative regulator of AHR activity, and that its specific loss in hepatocytes is sufficient to increase sensitivity to dioxin-induced steatohepatitis and lethality.